Emergence of measles virus genotype D8 amidst endemic B3 circulation in Uganda, 2023-2025 - Prossy Namuwulya; Irene Turyahabwe; Rena Nakyeyune; Molly Birungi; Phionah Tushabe; James Peter Eliku; Francis Aine; Jonathan Comfort Haumba; Mathias Ssenono; Lucy Nakabazzi; Maria Nabbuto; Jacob Mpiima; et al. (Elsevier, 2024)
Objectives: Measles remains a significant global health threat, with recurrent outbreaks, even in regions such as America, where the disease had been eliminated. Despite the availability of an effective and freely accessible vaccine, measles remains a global burden especially in children. The World Health Organization (WHO) estimated 107,500 measles-related deaths in 2023, with over 95% occurring in low- and middle-income countries reflecting fragile health systems. Uganda has similarly experienced persistent outbreaks since 2023. This study aimed at investigating the emergence of measles genotype D8 in Uganda for the first time, alongside the endemic measles genotype B3. Methods: To track measles circulating strains, molecular genotyping targeting the measles virus N450 region was performed on 137 specimens. Phylogenetic analysis of the sequences was carried out along with WHO reference sequences and GenBank selected sequences. Results: Alongside the endemic B3 genotype, genotype D8 was detected for the first time in Uganda, revealing co-circulation of both lineages. Conclusions: The detection of measles D8 alongside the endemic B3 indicated possible gaps in the existing surveillance system and vaccination coverage. These findings highlight the critical importance of molecular surveillance and the urgent need to enhance measles vaccination coverage.
Keywords: Measles; Outbreaks; Uganda; B3; D8